(untitled) (Applied Biological Research, 2022)
Capparis decidua is one of the important medicinal plants belonging to the family Capparaceae. The complete plastid genome of C. decidua, which is 157,573 bp long, was examined. In this study, we analyzed the complete plastid genome of species using high-throughput sequencing technology and assembled using NOVOPlasty. The large single copy (LSC), small single copy (SSC) and inverted repeats (IRa and IRb) were 85950, 18621 and 26526 bp long. There were 136 genes in the genome: 80 protein-coding genes, 31 tRNA genes, and 4 rRNA genes. The repeat sequences findings showed that chloroplast genome contained a variety of repeats, with palindromic repeat occurring more frequently. A set of 279 SSR were mined from the C. decidua genome and most of them possess mononucleotide repeat motifs (A/T).